2016
DOI: 10.14254/2071-789x.2016/9-1/3
|View full text |Cite
|
Sign up to set email alerts
|

Microenterprises and Significant Risk Factors in Loan Process

Abstract: Microenterprises-small companies with their own characteristic features-are a major component of the economic system, which brings positive effects on employment, increases the supply of goods and services, promotes the growth of competition in the market and performs other important functions in the economic system. Microenterprises face sufficient problems with the access to bank financing, which is a base for their sustainable growth. The aim of this paper was to define and quantify significant risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
0
16
0
3
Order By: Relevance
“…The business impact of SPMS is affected by information technology variables (Internet usage, ERPs, informational technology tools) (Bento et al, 2014). Especially ERP II -BI (Business Intelligence) represents the system that provides the ability to analyze business information in order to support and improve management decision making (Elbashir et al, 2008).…”
Section: Business Intelligence As a Key Knowledge Information Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The business impact of SPMS is affected by information technology variables (Internet usage, ERPs, informational technology tools) (Bento et al, 2014). Especially ERP II -BI (Business Intelligence) represents the system that provides the ability to analyze business information in order to support and improve management decision making (Elbashir et al, 2008).…”
Section: Business Intelligence As a Key Knowledge Information Supportmentioning
confidence: 99%
“…The examination of the measuring corporate performance issues is dedicated to many authors from different points of view: the relationship of the strategy and strategic orientation to the business performance (Morgan & Strong, 2003); the view of a strategic measurement performance system through strategic agenda and decision-making as a result of the process of (re)formulating strategy (Bisbe & Malagueño, 2012); the effect of strategic measurement performance system on the important attributes of the strategy formulating process (Gimbert et al, 2010); the effect of strategic performance measurement system of human resources and corporate results (Bento & White, 2014); the use of the process performance measurement (Tuček et al, 2013); the relations among customer satisfaction, customer loyalty and fi nancial performance of a commercial bank (Belás & Gabčová, 2016); the methodology for prediction and detection of the ways of solving demanding situations in managerial work, with obvious implications in performance of managers and in effi ciency of business performance management (Lajčin, Frankovský, & Štefko, 2012); the model of acquisition activity in fi nancial sector (Korauš et al, 2015); performance management and public corporate governance with regard to relationships with both external (stakeholders) and internal (politicians and management) actors (Romolini et al, 2015). Many other empirical studies realized around the world in recent years have also confi rmed the relationship between strategic planning and business performance (Rudd et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to (Belás, Vojtovič & Ključnikov, 2016) microenterprises struggle the most with the problems of entrepreneurship. They are most sensitive to changes in regional market conditions and are also exposed to a variety of financial risks (Ivanova & Latyshov, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results from studies of risks related to investment projects are reported in papers [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Forecasting risks and their behavior in dynamics are studied in paper [15]. The new look at risks and the construction of risk-free situations is given in article [16], which emphasizes the possibility of evaluating projects with minimal risk. The presentation of risks as a systemic object will make it possible to explore the behavior of an innovative project taking into consideration the types of risks [17,18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%